Constraints, Conflict and Counterproductive Work Behavior: Organizational Cynicism as a Mediator - Loh, Ashley; Alia, Azalea * (Malaysian Psychological Association, UKM, 2023)
Deviant workplace behavior is a pertinent issue as its detrimental impacts include financial losses for organizations. This study investigated the relationship between job stressors, organizational constraints (OC), interpersonal conflict (IC), organizational cynicism, and counterproductive work behavior (CWB). An online questionnaire was used to gather data from 141 Malaysians employed full-time (63 males, 78 females) aged between 19 and 62 years (M = 37.4; SD = 12.7) recruited through convenience and snowball sampling. Data was analyzed on IBM SPSS Statistics 25 through regression analysis. Mediation was examined using Baron and Kenny’s (1986) method. Results showed that both OC (β = .51) and IC (β = .39) were significant predictors of CWB. OC predicted organizational cynicism (β = .69), which in turn predicted CWB (β = .49). Organizational cynicism partially mediated OC and CWB relationship. Findings have practical implications in mitigating the negative impacts of CWB. Future studies can explore other mediating variables to further build upon the stressor-strain framework in the workplace.